Certolizumab pegol in rheumatoid arthritis: a review of Phase III clinical trials and its role in real-life clinical practice. (October 2011) - Horton, Sarah C; Das, Sudipto; Emery, Paul
Over the last decade, evidence has accumulated demonstrating the effectiveness of early suppression of inflammation in patients with rheumatoid arthritis. This is reflected in evidence-based guidelines recommending treatment according to a target of disease activity or patient function, the ultimate target being clinical remission. In the same period, an increasing number of biologic therapies have become available, providing multiple treatment options for patients failing conventional disease-modifying antirheumatic drugs. Recently two new TNF inhibitor agents have been licensed: certolizumab pegol and golimumab. This article will examine evidence of the efficacy and safety of certolizumab pegol in rheumatoid arthritis, its potential utility in the context of a market comprising multiple TNF inhibitor agents and where its use may be positioned in the future.